The Effect of a Higher Bias Gas Flow on Imposed T-Piece Resistance and Breathing in Preterm Infants at Birth - Kristel L. A. M. Kuypers; Lieve A. Willemsen; Sophie J. E. Cramer; Aidan J. Kashyap; Aidan J. Kashyap; Thomas Drevhammar; Thomas Drevhammar; Stuart B. Hooper; Stuart B. Hooper; Arjan B. te Pas (Frontiers Media S.A., 2022)
ObjectiveThe resistance created by the PEEP-valve of a T-piece resuscitator is bias gas flow dependent and might affect breathing in preterm infants. In this study we investigated the effect of a higher bias gas flow on the imposed inspiratory and expiratory T-piece resistance and expiratory breaking manoeuvres (EBM) in preterm infants during spontaneous breathing on CPAP at birth.MethodsIn a retrospective pre-post implementation study of preterm infants <32 weeks gestation, who were stabilised with a T-piece resuscitator, a bias gas flow of 12 L/min was compared to 8 L/min. All spontaneous breaths on CPAP within the first 10 min of starting respiratory support were analysed on a breath-by-breath basis to determine the breathing pattern of each breath and to calculate the imposed inspiratory and expiratory T-piece resistance (Ri, Re), flow rates and tidal volume.ResultsIn total, 54 infants were included (bias gas flow 12 L/min: n = 27, 8 L/min: n = 27) with a median GA of 29+6 (28+4-30+3) and 28+5 (25+6-30+3), respectively (p = 0.182). Ri and Re were significantly lower in the 12 L/min compared to 8 L/min bias flow group [Ri: 29.6 (26.1-33.6) vs. 46.4 (43.0-54.1) cm H2O/L/s, p < 0.001; Re: 32.0 (30.0-35.1) vs. 48.0 (46.3-53.9) cm H2O/L/s, p < 0.001], while the incidence of EBM [77% (53-88) vs. 77% (58-90), p = 0.586] was similar.ConclusionDuring stabilisation of preterm infants at birth with a T-piece resuscitator, the use of a higher bias gas flow reduced both the imposed inspiratory and expiratory T-piece resistance for the infant, but this did not influence the incidence of EBMs.